Geometric analysis evaluating the effect of tibial plateau leveling osteotomy position on postoperative tibial plateau slope - Kowaleski, M. P.; McCarthy, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
The tibial plateau leveling osteotomy procedure is designed to neutralize cranial tibial thrust by precisely reducing tibial plateau slope. Despite accurate intraoperative measurement and proximal tibial plateau segment rotation, postoperative assessment of tibial plateau slope frequently reveals a measured angle differing from the expected postoperative angle of 5.0 degrees. The effect of osteotomy placement on postoperative tibial plateau slope was evaluated by analysing its effect on the points utilized in tibial plateau slope measurement. Four osteotomy placements, encompassing the point dividing the intercondylar tubercles and an osteotomy centred on this point, were evaluated. The effect of centreing the osteotomy distal to the intercondylar tubercles was more closely evaluated. Formulae to determine the distance the intercondylar tubercles move, the angular shift of the tibial long axis after proximal tibial plateau segment rotation, and the relation of the final and intended tibial plateau slope were derived. Osteotomy placement centred on the proximal tibial long axis point results in a lack of movement or angular shift of the tibial long axis, after proximal tibial plateau segment rotation. Other osteotomy placements result in movement of the intercondylar tubercles, tibial long axis shift, and deviation from the expected postoperative tibial plateau slope. Centreing the tibial plateau leveling osteotomy on the proximal tibial long axis point is the mathematically correct position.
Keywords: Tibial; plateau; leveling; osteotomy; position